Correlation of Total IgE Level and Intensity of Infection among Soil Transmitted Helminthiasis Farmers in Klungkung Regency, Bali, Indonesia - Apsari, Putu Indah Budi; Arwati, Heny; Dachlan, Yoes Prijatna (Folia Medica Indonesiana, 2019)
The phenomena of increasing total IgE level in Soil Transmitted Helminthiasis and its protective role in resistance of infection remains unclear. The purpose of this study was to determine the correlation between total IgE and the intensity of Soil transmitted helminthiasis among farmers in these area. Total 162 farmer, age ranged 25-80 years participated in this cross sectional analytic study. Kato-Katz method was used to diagnose Soil Transmitted Helminthiasis and to determined infection intensity based on egg per gram (EPG). Total IgE levels were measured by enzyme linked flourescent assay (ELFA). The results of this study showed that 13,56% farmer positive for Soil Transmitted Helminthiasis, with single infection of Ascaris lumbricoides were 1,85%, 9,26% for Trichuris trichiura, 0,61% for Hookworm and mixed infection that were 1,23% for A.lumbricoides+T.trichiura 0,61% for A.lumbricoides+Hookworm. The intensity of infection were in mild category. Total IgE level in Soil transmitted Helminthiasis group was significantly different compared with noninfected group (p<0.05, t-test). There was significant correlation between EPG and total IgE level (r=0.667, p=0.001, Spearman test). As a conclusion total IgE level was significantly correlated with EPG, this fact can be used to develop management of Soil Transmitted Helminthiasis theraphy.